Applicability of fruit blanching and intermittent microwave-convective belt drying to industrial peel waste of different mango cultivars for the recovery of functional coproducts - Andreas Nagel (2018)
© 2017 Elsevier B.V. To exploit the full potential of industrial mango peel waste (MPW 0 ) as a starting material for the recovery of bioactive and functional coproducts despite its seasonality, it must be processed efficiently into a storable dried byproduct of uniform high quality, irrespective of impacts of different cultivars and ripeness. The focus of this feasibility study, performed on the pilot plant scale, was on technological options for three key process stages in the manufacture of dried mango peel (DMP) as a possible bulk commodity: fruit blanching, peel drying, and DMP packaging. Depending on cultivars, hot-water blanching of fruit (65–85 °C) before peeling proved inappropriate for peel color retention, but could even induce enzymatic browning until peel drying, and thus losses of bioactive compounds due to oxidative polymerization and insolubilization. Hence, this process step should be limited to brief washing of the fruit at maximally 65 °C to reduce microbial load. Intermittent microwave-convective drying (IMWC) of MPW 0 in a continuous belt dryer at high peel throughput was feasible at ambient air temperatures. Finalizing initial IMWC of MPW 0 by convective drying (CD, 80 °C) in the falling-rate period avoided local charring. Alternatively, MPW 0 had to be washed before IMWC to remove adherent pulp, but at the expense of soluble solids and β-carotene losses. Unlike the carotenoids, alk(en)ylresorcinols were hardly affected by IMWC. By washing MPW 0 , quality defects compared to CD-dried peel in terms of antioxidant capacity, water-holding capacity, and yield and quality of pectin were compensated. Adequate preprocessing plus IMWC was thus deemed to be a promising option, especially for biorefinery concepts including biogas production and congeneration. The minimal moisture barrier properties needed for flexible intermediate bulk containers were estimated from an 11-month shelf-life test of IMWC-dried peel in two climate zones.